Tableaux for some deontic logics with the explicit permission operator - Glavaničová, Daniela; Jarmużek, Tomasz; Klonowski, Mateusz; Kulicki, Piotr (Bulletin of the Section of Logic, 2022)
In this paper we present a tableau system for deontic logics with the operator of explicit permission. By means of this system the decidability of the considered logics can be proved. We will sketch how these logics are semantically defined by means of relating semantics and how they provide a simple solution to the free choice permission problem. In short, these logics employ relating implication and a certain propositional constant. These two are in turn used to define deontic operators similarly as in Andersonian-Kangerian reduction, which uses different intensional implications and constants.